2012
DOI: 10.2174/1877382601003010072
|View full text |Cite
|
Sign up to set email alerts
|

Techniques for Wound Healing with a Focus on Pressure Ulcers Elimination

Abstract: Pressure ulcers, also called decubitus ulcers, are a common challenge of humanity. They are wounds initiated by pressure on the skin that blocks circulation causing the skin and underlying tissues to die. Without care, pressure ulcers continue to grow in diameter and depth and are exceptionally difficult to heal. They have probably always existed, and are present on Egyptian mummies. Pressure ulcers are a serious health issue, very painful, a significant physiological challenge, can shorten the life of a patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 87 publications
1
10
0
Order By: Relevance
“…This discrepancy might be due to different characteristics of participants, disease condition of patients and sample size the participants. This study depicted that pressure ulcer was significantly associated (p<0.048) with age ,it was in line with a study conducted by Bergstron &Braden (25) ; but not supported by a survey conducted in the city of Belo Horizonte (Brazil), China, Nigeria and Bahir Dar (Felege Hiwot hospital) (25,3,9,7) . The reason not in lined to other studies might be the disease condition of patients and length of stay in hospital.…”
Section: Prevalence Of Pressure Ulcer With Anatomical Locationsupporting
confidence: 88%
See 3 more Smart Citations
“…This discrepancy might be due to different characteristics of participants, disease condition of patients and sample size the participants. This study depicted that pressure ulcer was significantly associated (p<0.048) with age ,it was in line with a study conducted by Bergstron &Braden (25) ; but not supported by a survey conducted in the city of Belo Horizonte (Brazil), China, Nigeria and Bahir Dar (Felege Hiwot hospital) (25,3,9,7) . The reason not in lined to other studies might be the disease condition of patients and length of stay in hospital.…”
Section: Prevalence Of Pressure Ulcer With Anatomical Locationsupporting
confidence: 88%
“…Higher prevalence in this study might be due to inappropriate nursing care, inadequate & very poor feeding habit and limited resource of pressure relieving devices. It was also found that the prevalence rate was lower than a study conducted in Brazil 16.9%, Germany 26.5%,Sweden 22.9%,Canada (Ontario) 25.7%, and Felege Hiwot hospital (Bahir Dar) 16.8 % (12,17,18,9,7) .This discrepancy might be due to different characteristics of participants, disease condition of patients and also the variation of study period &length of stay in hospital.…”
Section: Braden Scale Pressure Ulcer Risk Assessmentmentioning
confidence: 77%
See 2 more Smart Citations
“…Nose, chin, forehead, occiput, chest, back, and elbow are among the more common of the infrequent sites for pressure ulceration. [14] Presence and Location of Spasticity About half of the patients experienced muscle spasm mainly in lower limbs. This is similar to a report, [15] which indicated that contractures and spasticity often contribute by repeatedly exposing tissues to pressure through flexion of a joint.…”
Section: Location Of Pressure Ulcersmentioning
confidence: 99%